Role of the ρ meson in the description of pion electroproduction experiments; Physical Review C; Vol. 76, iss. 2 - Faessler A.; Gutsche Th.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Obukhovsky I. T. (2007, 2007)
Title screen